Road from Surakarta to Yogyakarta: History of Solo-Yogyakarta Road since 16th until 19th century - Lazuardi, Muhammad Fijar; Sunjayadi, R. Achmad (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This article describes the history of the road between Surakarta-Yogyakarta from the 16th until the 19th century. Historically, this road has connected several political entities in Java since the 16th century. By using the historical method, which consists of heuristic, sources criticism, interpretation, and historiography, this research attempts to explain the significance of historical events of the Solo-Yogyakarta Road according to historical records and sources. By doing literature research, this article finds that the Solo-Yogyakarta Road dates back to the establishment of Mataram as Pajang’s vassal. Later in the 17th century, this road became one of the diplomatic roads used by VOC ambassadors to the Mataram's Keraton, until the war of succession clashed in the early 18th century. When Prince Puger occupied the Plered palace in Mataram and Amangkurat III occupied the new palace in Kartasura, this street was also an important setting for several events in the war between the two. Later, the Solo-Yogyakarta road became a pilgrimage route for kings and royal families, so the existence of this road became symbolically important for Mataram's power.